The university and the tensions of inclusion as part of the ethos of social responsibility - Moreira, Ana Maria de Albuquerque; Techera, Andrea Tejera; Reis, Márcia Lopes [UNESP]; Schurmann, Sebastián (De Gruyter, 2021)
This chapter analyses the challenges for social responsibility in higher education in a scenario of growth of enrolments in three Latin American Countries: Argentina, Brazil, and Uruguay. After demonstrating the social inclusion policies in higher education in each country, the analysis is based on Bourdieu's concept of habitus.
Keywords: Habitus; Inclusion; Social responsibility